The Mexican indigenous experience – Legal pluralism: law outside the system - de la Torre Rangel, Jesús Antonio (2022)
The conception of Law in modernity is univocal: Law is the Written Law. Legal pluralism separates itself from the univocal theory of modernity; makes an epistemological break; accepts that the Law is not only the Law that produces the State, but also that juridicity that is born of the people, in their struggles and insurgencies. Here, diverse experiences of law production of diverse Mexican indigenous communities are narrated, from the uprising of the Zapatista Army of National Liberation (EZLN), which created autonomous municipalities and good government boards; it gives an account of the community experience of security, administration of justice and re-education of Montaña y Costa Chica from Guerrero; the community guard of Santa María Ostula is approached; the community police of Cherán is mentioned.